Change Controlling: Suggestions for the design of Change Controlling - Roland Rehn (Journal of Applied Leadership and Management, 2013)
Exploring the correlation of change controlling usage and success of change projects. Therefore this thesis investigates the characteristics of change controlling and their correlation with a successful measurement process. Furthermore, it aims to provide a proposal for a change controlling framework.
Keywords: 650; correlation of change controlling usage and success of change projects